Evaluation of Neudesin Level in A sample of Iraqi Patients with Hypothyroidism - Dawood, Ashgan Slman; Abed, Baydaa Ahmed; Farhan, Layla Othman; Salman, Isam N. (Iraqi Journal of Science, 2024)
Hypothyroidism, a condition where the thyroid gland does not produce enough thyroid hormone to maintain health, is most often caused by iodine deficiency in areas where iodine levels are low. However, in regions with adequate iodine, Hashimoto’s disease is the leading cause of hypothyroidism and thyroid failure. Neudesin in neuropeptide hormone, which is released by the brain and fat tissue, has both metabolic effects and neural. The study included ninety participants divided in two groups: in this study, the initial group comprised 30 female and 30 male individuals diagnosed with hypothyroidism, while the second group consisted of 15 female and 15 male participants who were healthy controls. The age range for both groups spanned from 30 to 60 years. The findings indicated that the hypothyroidism group exhibited significantly elevated levels of WHR, BMI, TC, TG, LDL, VLDL, TSH, and Neudesin compared to the control group. Particularly noteworthy, Neudesin displayed remarkable proficiency in distinguishing hypothyroidism patients from the control group, achieving an outstanding AUC 0.965. Using the findings, we deduced that the evaluation. Neudesin indicators may be beneficial for the diagnosis and response to therapy. The most sensitive and specific marker for hypothyroidism individuals is neudesin.